Effect of Yoga on Anxiety Levels among Medical Students During COVID-19 Pandemic - Prameswari, Yovita Rinda; Amita, Angela Shinta Dewi; Gracia, Isadora; Lilis, Lilis (Faculty of Medicine Universitas Padjadjaran, 2024)
Background: The COVID-19 pandemic became one of the factors that caused anxiety among medical students. Anxiety needs to be managed before it develops into a disorder. Yoga as a complementary therapy can reduce anxiety. This study aimed to determine the effectiveness of yoga on anxiety levels among medical students.Methods: This was a quasi-experimental study conducted in February–September 2022 and participated by medical students at the Atma Jaya Catholic University of Indonesia experienced anxiety. Participants were divided into two groups; an intervention group and a control group. Anxiety levels were measured using the Depression Anxiety Stress Scale 42 (DASS-42) questionnaire. The intervention provided was the Atma Jaya Yoga Intervention Studies (AJYOGIS) procedure for nine weeks. Yoga practice was performed online via Zoom and offline on campus. The Shapiro-Wilk test was used to test data distribution, Paired Sample T-Test and Wilcoxon Signed-Rank test to observe changes within groups. The changes between groups were analyzed using Unpaired Sample T-Test and Mann-Whitney test. A p-value of <0.05 was considered statistically significant.Results: Of the 36 medical students participated, the anxiety level of most participants was in the moderate category (41.7%). There was a significant decrease in anxiety scores in the intervention and control group after practicing yoga (p<0.05). However, there was no significant change in the anxiety category in the control group (p=0.231).Conclusion: Yoga can reduce anxiety levels, especially during the COVID-19 pandemic. Further detailed analysis with a larger sample size is needed to strengthen these findings.